Effect of TALC on mechanical properties of Polypropylene - Pham, Thi Hong Nga; Pham, Ba Phuc Loc; Vo, Van Tuan (Journal of Technical Education Science, 2018)
The extensive range of fillers used nowadays indicated the major significance of filler in the plastic industry. Although their original purpose was to lower the cost of the molding compounds; prime importance is now attached to selective modification of the properties of a specific plastic. With the aim of identifying the effect of Talc filler on mechanical properties of PP, the Talc powder which combined with PP at different portions of 10%, 20%, 30% by weight was studied in this paper. The tensile strength, flexural strength and hardness of samples were determined according to ASTM D638, ASTM D790 and ASTM D2240. The results show the decrease in the tensile strength, flexural strength comparing to those of pure PP; with the presence of 30% talc, the tensile strength decreased from 30.73 MPa of pure PP to 23.29 MPa, the flexural strength decreased from 49.31MPa to 47.62MPa. On the contrary, the hardness experienced an increase. The composites with 30% of talc had the highest hardness of 83.8HD, higher than the pure PP. In this study, the PP/Talc composites achieved the best comprehensive properties in presence of 10% Talc.